4-channel Coherently Combined Long-term-stable Ultrafast Thulium-doped Fiber CPA - Gaida, Christian; Stutzki, Fabian; Gebhardt, Martin; Heuermann, Tobias; Breitkopf, Sven; Main, Tino; Rothharde, Jan; Limpert, Jens (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Recent milestones in power-scaling of ultrafast fiber-based lasers were achieved by the simultaneous mitigation of thermal and nonlinear effects through the coherent combination of ultrafast pulses [1]. This technique is based on splitting the light into several spatially separated amplification channels that are subsequently coherently recombined into a single beam. Besides the performance scaling aspect, the laser wavelength is an important parameter for many applications, e.g. for high-field physics due to the quadratic wavelength-dependence of the ponderomotive potential [2]. Tm-doped fiber lasers have proven to be promising and relatively straightforward candidates for the realization of efficient high average- and peak-power ultrafast lasers in the 2-m wavelength region [3] , [4]. Here we demonstrate the coherent combination [1] , [5] of four thulium-doped fiber amplifiers. The fiber-based chirped pulse amplifier (CPA [6] ) delivers pulses with <120 fs full-width at half-maximum duration with up to 228J of pulse energy at a center wavelength of 1940 nm.
CRIS-Team Scopus Importer:2023-04-20